2015
DOI: 10.1108/ijopm-03-2013-0134
|View full text |Cite
|
Sign up to set email alerts
|

Achieving employee commitment for continuous improvement initiatives

Abstract: Purpose – Although prior research has found that employee participation is key to successfully implementing quality management initiatives (Baird et al., 2011; de Menezes, 2012; Lagrosen and Lagrosen, 2005), little research in operations management exists that investigates which management actions and behaviors lead to employee commitment to such initiatives. The purpose of this paper is to address this gap in the operations management literature by investigating which influence tactics are the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
84
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 53 publications
(93 reference statements)
6
84
1
7
Order By: Relevance
“…(Soltani and Wilkinson, 2010). This is in contrast with contemporary research (Lam et al, 2015) that recognised CI as the ongoing process improvement with crucial role in a TQM environment.…”
contrasting
confidence: 46%
See 4 more Smart Citations
“…(Soltani and Wilkinson, 2010). This is in contrast with contemporary research (Lam et al, 2015) that recognised CI as the ongoing process improvement with crucial role in a TQM environment.…”
contrasting
confidence: 46%
“…An appropriate organisational culture has been widely considered as necessity for any TQM practice including LSS (Kanpp, 2015;Antony, 2014, Zu et al, 2010Mosadegh rad, 2006), whilst more recently the gap in the empirical research examining the association between organisational culture and TQM practices has also been acknowledged (Lam et al, 2015;Baird et al, 2011). Other studies have suggested that organisational culture, leadership and behavioural aspects are soft critical factors in all TQM practices (Calvo-Mora et al, 2014;Laohavichien et al, 2011;Baird et al, 2011).…”
Section: Organisational Culture and Readiness For Lssmentioning
confidence: 99%
See 3 more Smart Citations